One for all, all for one: Social considerations in user acceptance of contact tracing apps using longitudinal evidence from Germany and Switzerland. (June 2022) - Abramova, Olga; Wagner, Amina; Olt, Christian M.; Buxmann, Peter
Abstract: We propose a conceptual model of acceptance of contact tracing apps based on the privacy calculus perspective. Moving beyond the duality of personal benefits and privacy risks, we theorize that users hold social considerations (i.e., social benefits and risks) that underlie their acceptance decisions. To test our propositions, we chose the context of COVID-19 contact tracing apps and conducted a qualitative pre-study and longitudinal quantitative main study with 589 participants from Germany and Switzerland. Our findings confirm the prominence of individual privacy calculus in explaining intention to use and actual behavior. While privacy risks are a significant determinant of intention to use, social risks (operationalized as fear of mass surveillance) have a notably stronger impact. Our mediation analysis suggests that social risks represent the underlying mechanism behind the observed negative link between individual privacy risks and contact tracing apps' acceptance. Furthermore, we find a substantial intention–behavior gap. Highlights: We model CTA acceptance by integrating social considerations into privacy calculus. A longitudinal study with 589 participants from Germany and Switzerland. Social risks (fear of mass surveillance) have a stronger impact than privacy risks. Social risks fully mediate the "privacy risks-CTA use" link. A substantial intention-behavior gap is revealed, with a nearly 40% dropout rate.